Interictal to ictal transition in human temporal lobe epilepsy: insights from a computational model of intracerebral EEG - Wendling, Fabrice (Lippincott Williams & Wilkins, 2005)

(untitled)
In human partial epilepsies, as well as in experimental models of chronic and/or acute epilepsy, the role of inhibition and the relationship between the inhibition and excitation and epileptogenesis has long been questioned. Besides experimental methods carried out either in vitro (human or animal tissue) or in vivo (animals), pathophysiological mechanisms can be approached by direct recording of brain electrical activity in human epilepsy. Indeed, in some clinical pre-surgical investigation methods like stereoelectroencephalopraphy (SEEG), intracerebral electrodes are used in patients suffering from drug resistant epilepsy to directly record paroxysmal activities with excellent temporal resolution (in the order of one millisecond). The study of neurophysiological mechanisms underlying such depth-EEG activities is crucial to progress in the understanding of the interictal to ictal transition. In this study, we relate electrophysiological patterns typically observed during the transition from interictal to ictal activity in human mesial temporal lobe epilepsy (MTLE) to mechanisms (at a neuronal population level) involved in seizure generation through a computational model of EEG activity. Intracerebral EEG signals recorded from hippocampus in five patients with MTLE during four periods (during interictal activity, just before seizure onset, during seizure onset and during ictal activity) were used to identify the three main parameters of a model of hippocampus EEG activity (related to excitation, slow dendritic inhibition and fast somatic inhibition). The identification procedure used optimization algorithms to minimize a spectral distance between real and simulated signals. Results demonstrated that the model generates very realistic signals for automatically identified parameters. They also showed that the transition from interictal to ictal activity can not be simply explained by an increase in excitation and a decrease in inhibition but rather by time-varying ensemble interactions between pyramidal cells and local interneurons projecting to either their dendritic or perisomatic region (with slow and fast GABA(A) kinetics). Particularly, during preonset activity, an increasing dendritic GABAergic inhibition compensates a gradually increasing excitation up to a brutal drop at seizure onset when faster oscillations (beta and low gamma band, 15 to 40 Hz) are observed. These faster oscillations are then explained by the model feedback loop between pyramidal cells and interneurons targeting their perisomatic region. These findings obtained from model identification in human TLE are in agreement with some results obtained experimentally, either on animal models of epilepsy or on the human epileptic tissue.